Copper-Catalyzed Intermolecular Aminooxygenation of Styrenes Using N-Fluorobenzenesulfonimide and Simple Alcohols - Hermosilla-Ibanez, P; Hermosilla-Ibanez, P (Wiley Blackwell, 2016)
The mild and fast copper-catalyzed radical and regioselective aminoalkoxylation of styrenes by using N-fluorobenzenesulfonimide and simple alcohols as nitrogen and alkoxy sources, respectively, was investigated. The aminoalkoxylated products obtained could be used in the synthesis of new compounds with possible activity as neurotransmitter receptor ligands. © 2016 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim